1992
DOI: 10.1038/bjc.1992.120
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies in the detection of bone marrow metastases in small cell lung cancer

Abstract: In conclusion, the monoclonal antibodies used in this study may be useful for diagnostic purposes when a suspicious looking infiltration is detected by CE. However, these antibodies could not detect metastatic tumour cells in the bone marrow sections from patients in whom CE did not reveal any tumour cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This result, however, could reflect the dismal prognosis of ED patients, since in our series positive BMA were more frequent in patients with extensive than limited disease (92.3 vs 41.2% respectively) (P = 0.005). We confirmed also that marrow positivity was associated with liver metastases, as previously reported (Skov et al, 1992) (Table 3). This may imply that liver involvement in patients with positive BMA is more frequent than found with conventional staging procedures.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This result, however, could reflect the dismal prognosis of ED patients, since in our series positive BMA were more frequent in patients with extensive than limited disease (92.3 vs 41.2% respectively) (P = 0.005). We confirmed also that marrow positivity was associated with liver metastases, as previously reported (Skov et al, 1992) (Table 3). This may imply that liver involvement in patients with positive BMA is more frequent than found with conventional staging procedures.…”
Section: Discussionsupporting
confidence: 80%
“…A growing body of evidence suggests that not only BM contamination by SCLC cells is far more frequent than previously shown by traditional cytohistological methods (Stahel et al, 1985;Leonard et al, 1990;Pasini et al, 1994bPasini et al, , 1995 but also that BM involvement may have clinical relevance (Leonard et al, 1990;Bucher et al, 1994;Pasini et al, 1994bPasini et al, , 1995. Immunocytochemistry is a convenient method for detecting BM micrometastases thanks to its simplicity, reliability and relative low cost (Leonard et al, 1990;Molino et al, 1991;Beiske et al, 1992;Skov et al, 1992;Pasini et al, 1994a), whereas other techniques, such as in vitro cultures of marrow cells (Pollard et al, 1981;Hunter et al, 1987;Everard et al, 1990) or magnetic resonance imaging (Trillet et al, 1989), are cumbersome, time-consuming and expensive.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Many studies on the detection of SCLC micrometastases in BMA have employed antibodies to NCAM (Frew et al 1986;Berendsen et al 1988;Hay et al 1988;Moss et al 1988;Trillet et al 1989;Leonard et al 1990;Beiske et al 1992;Skov et al 1992;Myklebust et al 1993a,b;Pasini et al 1994aPasini et al ,1995. In fact, NCAM (CD56, NKH-1, cluster-1 antigen) is expressed by almost all SCLCs (Souhami et al 1987(Souhami et al , 1991Stahel et al 1994) and in a variety of normal tissues (Cunningham et al 1987;Dalseg et al 1989;Patel et al 1989;Hida et al 1991;Lanier et al 1992), and in most tumors of neuroectodermal and mesodermal lineage (Patel et al 1989(Patel et al ,1991Moolenaar et al 1990;Tome et al 1991;Kern et al 1992;Miettinen and Cupo 1993;Ledermann et al 1994;Nakamura et al 1995;Pasini et al 1994aPasini et al ,1995.…”
mentioning
confidence: 99%
“…Evidence is accumulating not only that bone marrow microcontamination by SCLC cells is by far more common than assessed by traditional cytohistological methods (Berendsen et al 1988;Trillet et al 1989;Beiske et al 1992) but also that this involvement may have clinical relevance (Leonard et al 1990;Bucher et al 1994;Pasini et al 1994bPasini et al , 1995. In general, the immunocytochemical search for bone marrow micrometastases in SCLC patients has been performed on bone marrow aspirates (BMAs) using monoclonal antibodies (MAbs) directed against tumor-associated membrane antigens or cytokeratin polypeptides (Leonard et al 1990;Beiske et al 1992;Skov et al 1992;Pasini et al 1994a). Immunocytochemistry is the most simple, reliable, and inexpensive technique for detecting neoplastic microlocalizations in bone marrow (Molino et al 1991), whereas other reported methods, such as in vitro cultures of marrow cells (Pollard et al 1981;Hunter et al 1987;Everard et al 1990) or magnetic resonance imaging (Trillet et al 1989), are cumbersome, expensive, and time-consuming.…”
mentioning
confidence: 99%